2022
DOI: 10.1182/blood.2022015560
|View full text |Cite
|
Sign up to set email alerts
|

Ibrutinib improves survival compared with chemotherapy in mantle cell lymphoma with central nervous system relapse

Abstract: Central nervous system (CNS) relapse of mantle cell lymphoma (MCL) is a rare phenomenon with dismal prognosis, where no standard therapy exists. Since the covalent Bruton tyrosine kinase (BTK) inhibitor ibrutinib is effective in relapsed/refractory MCL and penetrates the blood–brain barrier (BBB), on behalf of Fondazione Italiana Linfomi and European Mantle Cell Lymphoma Network we performed a multicenter retrospective international study to investigate the outcomes of patients treated with ibrutinib or chemoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 47 publications
1
21
0
Order By: Relevance
“…IT injection for patients with LM is feasible because the IT technique is common and clinically used for pain control after surgery (65). This is supported by the previous studies in which IT-delivered chemotherapy was tested in patients with LM and CNS lymphoma (66,67). Our results support that allogeneic SC-based OV immunotherapy is widely applicable to varying forms of clinical metastases, including LM.…”
Section: Discussionsupporting
confidence: 83%
“…IT injection for patients with LM is feasible because the IT technique is common and clinically used for pain control after surgery (65). This is supported by the previous studies in which IT-delivered chemotherapy was tested in patients with LM and CNS lymphoma (66,67). Our results support that allogeneic SC-based OV immunotherapy is widely applicable to varying forms of clinical metastases, including LM.…”
Section: Discussionsupporting
confidence: 83%
“…7 The presence of blastoid morphology and a high-risk MIPI score increase the risk of central nervous system involvement in MCL, which has been associated with a poor prognosis, although more recently promising results have been reported with ibrutinib. 27,28 Biological factors…”
Section: Clinical Featuresmentioning
confidence: 99%
“…GI involvement is relatively common but its prognostic significance is unclear – one previous retrospective analysis compared patients with primary (isolated) GI MCL with non‐isolated GI cases and found that although primary GI MCL was often managed more conservatively, long‐term survival rates were very similar 7 . The presence of blastoid morphology and a high‐risk MIPI score increase the risk of central nervous system involvement in MCL, which has been associated with a poor prognosis, although more recently promising results have been reported with ibrutinib 27,28 …”
Section: Aggressive MCLmentioning
confidence: 99%
“…In this issue of Blood, Rusconi et al provide evidence that ibrutinib improves survival compared with chemotherapy that crosses the blood-brain barrier (BBB) in patients with central nervous system (CNS) relapse of mantle cell lymphoma (MCL). 1 The development of CNS involvement or CNS relapse poses a significant clinical challenge in the management of MCL. In a retrospective series, the overall incidence of CNS relapse in MCL is uncommon, reportedly in the range of 4% to 5% in unselected cohorts.…”
Section: Jia Ruan | Weill Cornell Medicinementioning
confidence: 99%